2015
DOI: 10.3390/molecules200915597
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Ring Opening Metathesis Copolymerization of Norbornene and Cyclopentene by Grubbs’ 1st-Generation Catalyst

Abstract: Statistical copolymers of norbornene (NBE) with cyclopentene (CP) were prepared by ring-opening metathesis polymerization, employing the 1st-generation Grubbs' catalyst, in the presence or absence of triphenylphosphine, PPh3. The reactivity ratios were estimated using the Finemann-Ross, inverted Finemann-Ross, and Kelen-Tüdos graphical methods, along with the computer program COPOINT, which evaluates the parameters of binary copolymerizations from comonomer/copolymer composition data by integrating a given cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Past studies have demonstrated that cyclopentene (C) and norbornene (N) will copolymerize with a variety of ROMP catalysts, and typically N is preferentially enchained over C. [16][17][18][19][20][21][22] None of these studies intended to demonstrate that C units could be enchained below [C] eq (≈1.2 m at room temperature [23] ), although close examination of the experimental conditions reveals that this was the case for at least one successful C-N copolymerization. [20] In several cases, [17][18][19][20][21][22] reactivity ratios (r C and r N , [17,18,21,22] or the product r C r N [19,20] ) were determined as a means to quantify the copolymerization process, but all of these analyses employed the classical terminal model of copolymerization [24][25][26] (or the dyad distribution resulting therefrom), which does not include the possibility of depropagation of either unit. As we will show below, this can lead to very large (order-of-magnitude) errors in r C (the reactivity ratio for the reversibly propagating monomer), and to a qualitatively incorrect description of certain features of the copolymerization (e.g., the limiting conversion at which propagation ceases).…”
Section: Doi: 101002/macp201800030mentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies have demonstrated that cyclopentene (C) and norbornene (N) will copolymerize with a variety of ROMP catalysts, and typically N is preferentially enchained over C. [16][17][18][19][20][21][22] None of these studies intended to demonstrate that C units could be enchained below [C] eq (≈1.2 m at room temperature [23] ), although close examination of the experimental conditions reveals that this was the case for at least one successful C-N copolymerization. [20] In several cases, [17][18][19][20][21][22] reactivity ratios (r C and r N , [17,18,21,22] or the product r C r N [19,20] ) were determined as a means to quantify the copolymerization process, but all of these analyses employed the classical terminal model of copolymerization [24][25][26] (or the dyad distribution resulting therefrom), which does not include the possibility of depropagation of either unit. As we will show below, this can lead to very large (order-of-magnitude) errors in r C (the reactivity ratio for the reversibly propagating monomer), and to a qualitatively incorrect description of certain features of the copolymerization (e.g., the limiting conversion at which propagation ceases).…”
Section: Doi: 101002/macp201800030mentioning
confidence: 99%
“…Past studies have demonstrated that cyclopentene (C) and norbornene (N) will copolymerize with a variety of ROMP catalysts, and typically N is preferentially enchained over C . None of these studies intended to demonstrate that C units could be enchained below [C] eq (≈1.2 m at room temperature), although close examination of the experimental conditions reveals that this was the case for at least one successful C–N copolymerization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that copolymer properties are correlated to copolymer structure, so, the elucidation and manipulation of structure (composition, monomer sequence distribution) and kinetics (propagation rate coefficients and reactivity ratios) are of major importance. An enormous amount of work, both experimental and theoretical, describes the significance of copolymerization in the field of polymer science …”
Section: Introductionmentioning
confidence: 99%
“…An enormous amount of work, both experimental and theoretical, describes the significance of copolymerization in the field of polymer science. [3][4][5][6][7][8][9][10][11][12] This study is focused on the Reversible Addition-Fragmentation chain Transfer (RAFT) copolymerization of N-vinylpyrrolidone (NVP) and 2-(dimethylamino)ethyl methacrylate (DMAEMA). RAFT is a powerful and broadly applicable method for copolymerization as it combines the benefits of conventional radical polymerization and that of living polymerization techniques.…”
mentioning
confidence: 99%